Sex sells, but at what cost? - Chin, Hui Shan (Nanyang Technological University, 2022)
Sex sells, but at what cost? is a journalism feature writing package that explores the rise of social media platforms that act as a medium for the proliferation of online sex content and the issues surrounding online sex work in Singapore. A subscription-based social media platform where creators sell their visual content, OnlyFans is home to creatives such as musicians and fashion bloggers but is mostly known for being an outlet for sexual content creators. The platform’s worldwide popularity has skyrocketed amid the COVID-19 pandemic. At the end of 2019, OnlyFans had 120,000 creators (Bosely, 2020). Today, OnlyFans has more than 170 million registered users andover 1.5 million content creators (The Straits Times, 2022). In Singapore, there are more than 110 OnlyFans content creators. These content creators post sexually provocative and even explicit photographs and videos on their accounts for a price. For their subscribers, that price is a monthly subscription fee ranging from $6 to $67, set by the creators. But the price these content creators pay is possible jail time. Under Section 292 of the Penal Code, it is an offence to produce or distribute obscene material in Singapore. Surprisingly, we also uncovered the prevalence of sexual content on other social media platforms such as Reddit and Twitter in Singapore. OnlyFans is an additional platform that facilitates the process of uploading and selling sexually explicit content. This meant that selling nudes is not a new occurrence in Singapore but instead the presence of OnlyFans helped to accelerate this trend. Monetary gratification aside, these content creators face issues that money cannot solve such as getting harassed on the streets or having derogatory insults hurled at them. Despite these drawbacks, content creators are not defeated as the ultimate goal for many is to create a safe space to promote sex-positivity without any harsh judgment. In our package, we explored several topics surrounding the rise of online sex content creators — their main motivations for doing so, the problems they face, the legality of engaging in such work in Singapore and the role society and parents can play to educate the younger generation on sex.